2014
DOI: 10.3354/dao02695
|View full text |Cite
|
Sign up to set email alerts
|

Philometra floridensis (Nematoda: Philometridae) damages ovarian tissue without reducing host (Sciaenops ocellatus) fecundity

Abstract: The parasitic nematode Philometra floridensis infects the ovary of its only host, the economically important fish species Sciaenops ocellatus, but the factors influencing host susceptibility and potential pathogenic effects are unknown. Here we report new information on these topics from evaluations of infected and uninfected hosts collected from the northeastern Gulf of Mexico. Fish length and age were evaluated vis-à-vis nematode prevalence to check for ontogenetic differences in host susceptibility. To eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In fact, a higher prevalence of Philometra sp. in the ovary than in the testes was found in Paralichthys adspersus , Glaucosoma ebraicum , Cynoscion nebulosus , Genypterus chilensis and Sciaenops ocellatus (Oliva et al., ; Hesp et al., ; Perez et al., ; Chávez and Oliva, ; Bakenhaster et al., ). Philometrids often affect only one gender of a given species (Moravec and de Buron, ); similarly in this case, no male gonads of P. erythrinus were parasitized.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, a higher prevalence of Philometra sp. in the ovary than in the testes was found in Paralichthys adspersus , Glaucosoma ebraicum , Cynoscion nebulosus , Genypterus chilensis and Sciaenops ocellatus (Oliva et al., ; Hesp et al., ; Perez et al., ; Chávez and Oliva, ; Bakenhaster et al., ). Philometrids often affect only one gender of a given species (Moravec and de Buron, ); similarly in this case, no male gonads of P. erythrinus were parasitized.…”
Section: Discussionmentioning
confidence: 98%
“…In mammals and birds, degeneration processes are often followed by formation of giant cells, and in fish, their presence is only rarely mentioned mostly with nematode infections. In these rare instances, Molnár, Szakolczai, and Vetési () observed them in the swim bladder with Anguillicola crassus Kuwahara, Niimi & Itagaki, 1974 infection due to invasion of second stage larvae, while Bakenhaster, Lowerre‐Barbieri, Kiryu, Walters, and Fajer‐Avila () found giant cell formations with Philometra infections of fish. No information is available about giant cell formation at infection of fish in parasitic copepods.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the effects of Philometra on fish ovaries are uncommon, as are those addressing parasitism of fish gonads in general [16]. Bakenhaster et al [18] reported that nematode (Philometra floridensis) parasite infection resulted in reduced fecundity in Sciaenops ocellatus as a result of the effective volume of the ovaries was reduced. Infected ovaries of Channa punctata exhibited necrosis and decrease in the yolk formation due to the disappearance of vitellogenic oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The present observation attributes towards that nematode P. piscaria larvae resulted in a decrease in the formation of atretic follicles during reproductive period potential of infected host fish. Bakenhaster et al [18] reported the histopathological changes caused by the Philometra floridensis in Sciaenops ocellatus which revealed damaged oocytes showing signs of necrosis, damaged and disrupted germinal epithelium, liquefaction of yolk globules and reduction in yolk formation in infected ovaries.…”
Section: Discussionmentioning
confidence: 99%